2021
DOI: 10.1080/21663831.2021.1878475
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of sluggish diffusion in FCC Al0.25CoCrFeNi high-entropy alloy

Abstract: To validate the 'sluggish diffusion' in high-entropy alloys, interdiffusion coefficients of individual elements and tracer diffusion coefficient of Ni were experimentally determined in FCC Al 0.25 CoCrFeNi alloy. The tracer diffusion coefficient was determined without the application of radio-tracers using a novel analytical method proposed by Belova et al. based on linear response theory coupled with Boltzmann-Matano approach and Gaussian distribution function. Sluggish diffusion kinetics was not observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Based on the sluggish diffusion postulate, diffusion should be slow in alloys with higher configurational entropy of mixing. If so, average effective interdiffusion coefficients Ni in Co-Cr-Fe-Ni, Al-Co-Cr-Fe-Ni [3,19] , and Al-Co-Cr-Fe-Ni- Mn [4] alloys. The…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the sluggish diffusion postulate, diffusion should be slow in alloys with higher configurational entropy of mixing. If so, average effective interdiffusion coefficients Ni in Co-Cr-Fe-Ni, Al-Co-Cr-Fe-Ni [3,19] , and Al-Co-Cr-Fe-Ni- Mn [4] alloys. The…”
Section: Discussionmentioning
confidence: 99%
“…Co and Deff Fe is the highest in quinary Al-Co-Cr-Fe-Ni alloy and contradicts the sluggish diffusion hypothesis based on Deff i determination. Figure 7 compares the temperature-dependent tracer diffusion coefficient of Ni, D Ã Ni in various quaternary and quinary FCC HEAs, i.e., CoCrFeNi [18] , CoCrFeNiMn 0.5 [11] , CoCrFeNiMn [18] , and Al 0.25-CoCrFeNi [19] . The D Ã Ni is the lowest in quaternary CoCr-FeNi alloy and the highest in quinary Al 0.25 CoCrFeNi alloy.…”
Section: Deffmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have reported that the main phase of a high-entropy alloy is of type B2, to which the structure of the Ni2MnGa-based FSMAs matrix belongs [15][16][17][18][19]. These high-entropy alloys exhibit excellent mechanical and physical properties, which is due to the combination of a high degree of alloying elements in the solution and a sluggish diffusion effect [20]. Lattice distortion in a high-entropy alloy generally leads to increased diffusion activation energies in the lattice, which, in turn, reduces the effective diffusion rate of the atoms.…”
Section: Introductionmentioning
confidence: 99%